The status of private military companies under international humanitarian law; towards a new convention - Daniels, Caroline (Centre for Law and Society, 2026)
This chapter will discuss different attempts made by various authors to categorize or subdivide actors in the private military sector and point out why these distinctions are problematic. It further seeks to provide for a definition of private military companies that is workable under international humanitarian law. It does so while at the same time recognizing that the purpose of international humanitarian law is to limit the effects of armed conflict by protecting persons who are not, or are no longer, participating in the hostilities and by restricting the means and methods of warfare. It is clear that private military companies offer services of a sophisticated nature and of a wide range, that there is an apparent wide demand for their services from a host of actors and that their operations are often transnational22. However, because of a lack of universally agreed upon definitions, understanding and defining private military is a daunting task.